The Profile of Students' Concept Mastery and Students' Perception using Semantic Network Analysis in Learning Global Warming - Almira Rizky Pratami, - (2020)
Students' concept mastery is one of the most essential elements in learning science. Since capability to master the subject can be seen through the concept of mastery. Another essential element that needs to be addressed in science education is students' perception as a learner. In order to ensure successful and substantive process of learning, it will be easier for the teacher to understand how the students perceive a specific concept in science. However, this research aims to investigate the profile of students' concept mastery and students' perception in learning global warming. For answering the research problem, 241 students from an Islamic-based junior high school were participated in this research. Students' concept mastery was analyzed by using 30 number of test items which consist of six level of cognitive domains. Meanwhile students' perception was determined through students' response from an open-ended essay test which questioning how the students define global warming topic. And the responses from the students were examined using semantic network analysis method. As the result, students' concept mastery showed diversity based on the level of cognitive domain, and the subtopic of global warming. For students' perception, there three statements obtained from the students' answer to represent how the students perceive the global warming topic.